3-5(x+7)+8=4x-12x+2(x-3)

Simple and best practice solution for 3-5(x+7)+8=4x-12x+2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-5(x+7)+8=4x-12x+2(x-3) equation:


Simplifying
3 + -5(x + 7) + 8 = 4x + -12x + 2(x + -3)

Reorder the terms:
3 + -5(7 + x) + 8 = 4x + -12x + 2(x + -3)
3 + (7 * -5 + x * -5) + 8 = 4x + -12x + 2(x + -3)
3 + (-35 + -5x) + 8 = 4x + -12x + 2(x + -3)

Reorder the terms:
3 + -35 + 8 + -5x = 4x + -12x + 2(x + -3)

Combine like terms: 3 + -35 = -32
-32 + 8 + -5x = 4x + -12x + 2(x + -3)

Combine like terms: -32 + 8 = -24
-24 + -5x = 4x + -12x + 2(x + -3)

Reorder the terms:
-24 + -5x = 4x + -12x + 2(-3 + x)
-24 + -5x = 4x + -12x + (-3 * 2 + x * 2)
-24 + -5x = 4x + -12x + (-6 + 2x)

Reorder the terms:
-24 + -5x = -6 + 4x + -12x + 2x

Combine like terms: 4x + -12x = -8x
-24 + -5x = -6 + -8x + 2x

Combine like terms: -8x + 2x = -6x
-24 + -5x = -6 + -6x

Solving
-24 + -5x = -6 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-24 + -5x + 6x = -6 + -6x + 6x

Combine like terms: -5x + 6x = 1x
-24 + 1x = -6 + -6x + 6x

Combine like terms: -6x + 6x = 0
-24 + 1x = -6 + 0
-24 + 1x = -6

Add '24' to each side of the equation.
-24 + 24 + 1x = -6 + 24

Combine like terms: -24 + 24 = 0
0 + 1x = -6 + 24
1x = -6 + 24

Combine like terms: -6 + 24 = 18
1x = 18

Divide each side by '1'.
x = 18

Simplifying
x = 18

See similar equations:

| .5x+0=6 | | 4(x+4y)(x-4y)= | | 2z-7=8 | | g(x)=9x-6 | | 4p+9=29 | | 24-x+x=24 | | -(8+y)=2y-8-y | | -2(7x-3)+9x=6+5(2x-1) | | 4t-0.07=-0.55 | | X^2+4x-y^2-6y-12=0 | | 4p+9=29 | | 4t-0.07=-0.55 | | -(8+y)=2y-8-y | | 6(7a+1)=132 | | 1200=2000*r*10 | | f(x)=3x^2-39x+36 | | 23x+3=49 | | 12x-15y=60 | | 7x=5a | | 1200=200*r*10 | | 4y+1=4 | | 4(2x-9)+61=-5(x-9)+16x-29 | | 24+3(-6)=8x-74 | | 4x+3x^2=6 | | 6u-14=14u | | 6(6b+7)= | | 84=-3(6r+8) | | 35=6y-1 | | 5x+10=90+x | | 46=7z+4 | | 0.8d+0.4=-5.2 | | 3(y+6)-8(5y-6)=-37y+4 |

Equations solver categories